The Expected Impact of Applying the Insurance Contracts Standard (IFRS 17) in the Solvency and Profitability of Insurance Companies listed on the Amman Stock Exchange - HAMZA , MOHYEDIN; OBEID , AHMAD; HADDAD , HOSSAM; Binsaddig , Ruaa; HAMID _ HISHAM , ABDUL (Journal of Ecohumanism, 2024)
This study aimed to identify the expected impact of applying International Financial Reporting Standard No. 17 on the solvency and profitability of the insurance companies listed on the Amman Stock Exchange. The descriptive analytical approach was used to achieve the study’s aim. The study used the questionnaire as a tool, where the study population consisted of all insurance companies listed on the Amman Stock Exchange. In contrast, the study sample included heads of accounts departments and actuaries working in insurance companies and accountants, and 33 questionnaires were distributed to insurance companies. One of the most important findings of this study was that there is a relationship between the independent variable (application of IFRS No. 17) and the dependent variable (solvency) in the insurance companies listed on the Amman Stock Exchange. And that there is a relationship between the independent variable (application of International Financial Reporting Standard No. 17) and the dependent variable (profitability) in the financial and service insurance companies listed on the Amman Stock Exchange. One of the most important recommendations of the study is the need for insurance companies to be keen to provide employees with ongoing experimental courses to remove the ambiguity surrounding some of the provisions of International Financial Reporting Standard No. 17.